Processes of European (Dis)Integration in Context of New Medievalism - Spalińska, Aleksandra (European Journal of Multidisciplinary Studies, 2018)
What is the source of the European Union’s crisis? Are disintegrating tendencies so serious? How the scope and content of member states’ sovereignty has changed within the years of integration process? The paper puts out a thesis that the answer to these questions can be found in the concept of new medievalism. This concept allows us to look at the EU from the perspective of historiosophy and civilization studies as well as globalization processes and qualitative changes in international politics. More broadly, this concept concerns the entire West, regarding social, political and economic changes which affect the position of western civilization in terms of its global domination. The “New Middle Ages” (another name for “new medievalism” in civilization studies) also refers to the European integration theory, providing a fresh look at the European history (this concept strongly refers to history) and interpretation of the presence at once. In the field of European Studies known is model of Europe as neo-medieval Empire, which provides the theoretical apparatus for research on changes of politics and power in Europe. The concept of new medievalism also investigates the risks of disintegration – that’s why it helps to understand the possible consequences of EU’s breakup. The aim of the paper is to present the interpretations of new medievalism, regarding the causes and possible outcomes of EU’s disintegration.
Keywords: European integration, disintegration, new medievalism, the West, civilization, globalization